What Expert Say about Empowering Human Resources in Supporting Leadership Function in Higher Education in the 21st Century - Eric Hermawan; Antoni Ludfi Arifin (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
In Indonesia, universities and non-formal education institutions play an essential role in creating leadership qualities in both colonial and modern time. Although these two education models have different supports, the resulting figures are expected to be involved in community development with intervention through research and community service with the budget and recognition given to them. This qualitative study was going to understand what research evidence says about the leadership role in higher education. To ascertain how these educational institutions' involvement and role are. The researchers have conducted electronic searches on online data sources such as the Google Scholar application, ERIC Publications, and Microsoft Academic for publications from 2010 to 2021. Furthermore, analyzing the data by involving understanding the problem, coding the data. Evaluation and in-depth interpretation to obtain valid and reliable findings. Based on the discussion of the findings data and previous research evidence, the researchers reported the results, the transition period to a more advanced future, and higher education's role in more strategic and dynamic planning. Higher education leaders must work to foster the public by encouraging lecturers and faculty with study data and dedication to achieve development goals towards success. They take great responsibility for the success of nation-building in all directions. Thus, these findings become an essential input in developing the role of higher education leadership. Keywords: Empowering Human Research, Leadership Function, Higher Education